Self-Efficacy Beliefs of Novice French as a Second Language Teachers: A Case Study of Ontario Teachers - Cooke, Shelley; Faez, Farahnaz (Canadian Journal of Applied Linguistics / Revue canadienne de linguistique appliquée)

(untitled) (University of New Brunswick, 2018)
The purpose of this study was to examine the self-efficacy beliefs of novice elementary French as a second language (FSL) teachers. A mixed methods approach was used to investigate self-efficacy appraisals of core French (n = 14) and French immersion (n = 13) teachers in delivering instruction in FSL programs. A questionnaire was administered that explored teachers’ self-perceived efficacy in four categories: general teaching methodology, second language pedagogy, language proficiency, and cultural knowledge.  Findings revealed that both groups of participants did not perceive themselves to be particularly confident in delivering instruction upon completion of their teacher education programs. The self-perceived confidence in FSL teaching abilities of both groups increased with classroom experience. However, French immersion teachers reported a higher sense of efficacy than their core French colleagues in all four categories. Implications of the findings for core French and French immersion programs as well as FSL teacher preparation programs are discussed.